2018
DOI: 10.1002/chem.201804393
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Photophysical Properties of Symmetric Squarylium Dyes: Investigation on the Halogen Modulation Effects

Abstract: As eries of symmetric squarylium dyes (SQDPA-X) with different halogen (X = F, Cl, Br,I )s ubstituents have been developed.T he photophysical properties could be facilely tuned by the halogen modulation effects. The strategyo fi ncorporating different halogen substitutions into AIE activel uminogens enables af acile approachf or exploring new intriguing organicf luorescent dyes.Organicf luorescent dyes have gained increasing interesto n account of their substantial applicationsi no rganic light-emitting diodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The intrinsic oxygen atoms in the skeleton of squaric acid can act as natural functional sites for framework construction and selective molecular recognition through hydrogen bonds (H bonds) or Lewis acid/base interactions with special guest species, without the need for postsynthetic modification . In addition, a variety of squaraines (SQs) dyes derived from squaric acid exhibit favorable photophysical properties with intense absorption and emission in the wide range from visible to near infrared, which are sensitive to the surrounding environment. , Recently, a new type of SQs have been reported to exhibit unique solid-state tunable luminescence properties, which can be modulated through control of molecular excited-state vibration and electron behavior . Some of these SQs could achieve temperature-/solvent vapor-triggered SCSC reversible structure transformation associating with tunable luminescence behavior, , implying their structural flexibility and structure-related luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic oxygen atoms in the skeleton of squaric acid can act as natural functional sites for framework construction and selective molecular recognition through hydrogen bonds (H bonds) or Lewis acid/base interactions with special guest species, without the need for postsynthetic modification . In addition, a variety of squaraines (SQs) dyes derived from squaric acid exhibit favorable photophysical properties with intense absorption and emission in the wide range from visible to near infrared, which are sensitive to the surrounding environment. , Recently, a new type of SQs have been reported to exhibit unique solid-state tunable luminescence properties, which can be modulated through control of molecular excited-state vibration and electron behavior . Some of these SQs could achieve temperature-/solvent vapor-triggered SCSC reversible structure transformation associating with tunable luminescence behavior, , implying their structural flexibility and structure-related luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic route of Y-1 and Y-2 is shown in Scheme 1. The intermediates 1 and 2 are prepared according to literatures [34][35][36][37].…”
Section: Synthesis Of Benzothiadiazole Dyesmentioning
confidence: 99%
“…On the other hand, halogenation is a feasible strategy to influence the photophysical properties of organic dyes, such as photostability, molecular packing, emission efficiency, and so on [38–48] . Some studies have also been conducted and reported to investigate the effects of halogen substitutions on AIEgens [49–55] .…”
Section: Introductionmentioning
confidence: 99%